Public private partnership in social sector in India: In quest of a policy - Singh, U.B. (2008)
Infrastructure development at local level should comprise social infrastructure like health and education and services like water supply, sewerage and sanitation. The social sector development is overwhelmed with welfare hence the private partner in the PPP may not be enthusiastic to join hands with local institutions for the provision and delivery of services. For a pragmatic implementation of PPP in this sector new policy initiatives would be required in order to scale up and broaden the PPP programme. Broad policy initiatives would enable government to announce more clearly the institutional framework for PPP. This could include the regulation, oversight and evaluation of PPP. - Reproduced.
Keywords: Public private partnership - India; Public private partnership